(untitled) (Eurasian Scientific Herald, 2022)
Hypertension is a major risk factor for cardiovascular disease and mortality, which is one of the major public health problems worldwide. Hypertension causes a number of pathophysiological ocular modifications that significantly affect the retina, choroid and optic nerve circulations, which lead to a number of ocular defects. The retina is the only site in the body where the microvascular can be directly tested, providing valuable information about hypertension associated with systemic risks. In the process of circulatory disorders in the capillaries, degeneration of the nervous tissue occurs, which is especially sensitive to any negative changes in metabolism